Impact on alcohol selection and online purchasing of changing the proportion of available non-alcoholic versus alcoholic drinks: A randomised controlled trial. - Natasha Clarke; Anna K M Blackwell; Jennifer Ferrar; Katie De-Loyde; Mark A Pilling; Marcus R Munafò; Theresa M Marteau; Gareth J Hollands (PLoS Medicine)
Background Increasing the availability of non-alcoholic options is a promising population-level intervention to reduce alcohol consumption, currently unassessed in naturalistic settings. This study in an online retail context aimed to estimate the impact of increasing the proportion of non-alcoholic (relative to alcoholic) drinks, on selection and purchasing of alcohol. Methods and results Adults (n = 737) residing in England and Wales who regularly purchased alcohol online were recruited between March and July 2021. Participants were randomly assigned to one of 3 groups: "25% non-alcoholic/75% alcoholic"; "50% non-alcoholic/50% alcoholic"; and "75% non-alcoholic/25% alcoholic," then selected drinks in a simulated online supermarket, before purchasing them in an actual online supermarket. The primary outcome was the number of alcohol units selected (with intention to purchase); secondary outcomes included actual purchasing. A total of 607 participants (60% female, mean age = 38 years [range: 18 to 76]) completed the study and were included in the primary analysis. In the first part of a hurdle model, a greater proportion of participants in the "75% non-alcoholic" group did not select any alcohol (13.1%) compared to the "25% non-alcoholic" group (3.4%; 95% confidence interval [CI] -2.09, -0.63; p < 0.001). There was no evidence of a difference between the "75% non-alcoholic" and the "50% non-alcoholic" (7.2%) groups (95% CI 0.10, 1.34; p = 0.022) or between the "50% non-alcoholic" and the "25% non-alcoholic" groups (95% CI -1.44, 0.17; p = 0.121). In the second part of a hurdle model in participants (559/607) selecting any drinks containing alcohol, the "75% non-alcoholic" group selected fewer alcohol units compared to the "50% non-alcoholic" (95% CI -0.44, -0.14; p < 0.001) and "25% non-alcoholic" (95% CI -0.54, -0.24; p < 0.001) groups, with no evidence of a difference between the "50% non-alcoholic" and "25% non-alcoholic" groups (95% CI -0.24, 0.05; p = 0.178). Overall, across all participants, 17.46 units (95% CI 15.24, 19.68) were selected in the "75% non-alcoholic" group; 25.51 units (95% CI 22.60, 28.43) in the "50% non-alcoholic" group; and 29.40 units (95% CI 26.39, 32.42) in the "25% non-alcoholic" group. This corresponds to 8.1 fewer units (a 32% reduction) in the "75% non-alcoholic" compared to the "50% non-alcoholic" group, and 11.9 fewer alcohol units (41% reduction) compared to the "25% non-alcoholic" group; 3.9 fewer units (13% reduction) were selected in the "50% non-alcoholic" group than in the "25% non-alcoholic" group. For all other outcomes, alcohol selection and purchasing were consistently lowest in the "75% non-alcoholic" group. Study limitations include the setting not being entirely naturalistic due to using a simulated online supermarket as well as an actual online supermarket, and that there was substantial dropout between selection and purchasing. Conclusions This study provides evidence that substantially increasing the proportion of non-alcoholic drinks-from 25% to 50% or 75%-meaningfully reduces alcohol selection and purchasing. Further studies are warranted to assess whether these effects are realised in a range of real-world settings. Trial registration ISRCTN: 11004483; OSF: https://osf.io/qfupw.